The Discovery of Chinese Literature (Wenxue) - Yu, Laiming. author. aut Link
XII, 132 p. 2 illus.
Keywords: This book traces the origin and evolvement of two Chinese characters “wenxue”(literature) by using the methods of conceptual history and historical and cultural semantics, and by taking the evolution and changes of the concept of the these two characters and their interpretations in the west as a window, and re-examining the contemporary morphology of concept evolution in the historical context of concept generation and development to discover the historical and cultural connotations hidden behind the characters, so as to embark on a vivid journey to explore the history of literary thought, discipline and culture. The entire book is woven with the concept of “literature” at its core. Following the author's analysis and interpretation, an interlocking and orderly network of description of ancient and modern, Chinese and foreign unfolds. In this context, the chapters are progressive and mutually responsive, forming an organic whole which is connected at the beginning and the end. For those readers who are trying to understand how Chinese “wenxue” evolved from one of the “four disciplines of Confucius” into a modern discipline and concept, this book will provide the most detailed, in-depth, and vivid historical picture. Laiming Yu, Doctor of Chinese Literature, post-doctor in History, is now a Luojia Distinguished Professor and doctoral supervisor at Wuhan University, the deputy director of the Center of Traditional Chinese Cultural Studies, Wuhan University, and also a member of the Academic Committee of Wuhan University and the deputy director of the Professor Committee of the Academy of Humanities and Social Sciences. .